Low-cavity power encapsulation electronic solder material and vacuum reflow method thereof

CN122913646APending Publication Date: 2026-10-16SUZHOU JIAGU NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611211720.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但现有焊接材料的配方设计未与真空回流的工艺特性进行匹配优化:一方面,焊剂的活化温度区间与焊料熔化区间高度重叠,真空抽取时大量活性组分随气体快速挥发流失,导致焊料润湿性下降,界面易出现虚焊与润湿不良;另一方面,普通锡银铜焊料的熔融态表面张力较高,气泡逃逸阻力大,即使施加真空仍有大量微空洞残留于界面处

Benefits of technology

本方案通过焊接材料配方优化与真空回流工艺的协同设计,针对性解决了功率封装焊接界面空洞率高、高温可靠性不足的核心问题。在材料体系上,引入镧、铈、锶三类稀土元素协同作用,既细化焊料凝固组织、抑制界面金属间化合物过度生长,又有效降低熔融焊料的表面张力,为气泡逸出提供动力学条件;氢化松香基焊剂体系设计了匹配的温度 - 粘度曲线,常温下呈高粘度固态,无需冷藏即可稳定储存,活化区间与真空脱泡阶段精准对应,兼顾氧化膜去除效果与焊剂保留率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913646A_ABST
    Figure CN122913646A_ABST
Patent Text Reader

Abstract

The application discloses a kind of low cavity power package electronic welding materials and vacuum reflow method thereof, belong to electronic packaging welding technical field.The welding material is with tin silver copper alloy as matrix, add lanthanum, cerium, strontium rare earth modification component, collocation hydrogenated rosin, polyethylene glycol, composite organic acid, microcrystalline wax and so on constitute the flux system, with the characteristics of normal temperature storage stability, low surface tension of molten state.Its vacuum reflow method includes substrate pretreatment and solder precision printing, pre-evacuation low-temperature preheating activation, gradient temperature vacuum degassing treatment, high vacuum constant temperature reflow welding, five steps of segmented vacuum cooling shaping, bubble in welding system is discharged by the synergistic matching of material formula and vacuum process.The application can reduce the total cavity rate of power packaging welding interface to below 3%, while improving the reliability of joint high-temperature service, suitable for packaging welding process of various power electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic packaging welding technology, and more specifically to a low-void power packaging electronic welding material and its vacuum reflow method. Background Technology

[0002] Power electronic packaging is a core component of power electronic device manufacturing. The performance of soldering materials and reflow processes directly determines the thermal conductivity, mechanical reliability, and long-term service life of power modules. As third-generation semiconductor devices rapidly develop towards higher power density, higher junction temperature, and miniaturization, the solder interfaces between the chip and the substrate, and between the substrate and the heat sink, need to withstand higher thermal loads and mechanical stresses, placing far more stringent requirements on solder density, connection strength, and thermal stability than on traditional devices.

[0003] Currently, the mainstream approach in power packaging is to use tin-based solder paste combined with air reflow or conventional vacuum reflow processes for connection. Existing commercial soldering materials mostly use tin-silver-copper eutectic alloys as the solder base, coupled with a common rosin-based flux system. Under conventional air reflow conditions, gaseous products such as carbon dioxide and water vapor generated by the thermal decomposition of the flux are easily trapped inside the molten solder, forming solder voids of varying sizes upon cooling. Industry data shows that the total void ratio at the solder interface of air reflow processes is typically above 10%. Large-area voids severely block heat conduction paths, causing localized increases in thermal resistance and abnormal junction temperatures in power devices, ultimately leading to overheating failure. To reduce the void ratio, the industry has widely adopted vacuum reflow processes, which remove internal gases by drawing a vacuum during the solder melting stage. However, the formulation design of existing soldering materials has not been optimized to match the process characteristics of vacuum reflow. On the one hand, the activation temperature range of the flux highly overlaps with the melting range of the solder. During vacuum extraction, a large number of active components are rapidly lost with the gas, resulting in decreased solder wettability and easy occurrence of cold solder joints and poor wetting at the interface. On the other hand, ordinary tin-silver-copper solder has a high molten surface tension and large resistance to bubble escape. Even with vacuum, a large number of microvoids remain at the interface. In addition, traditional solder paste is a viscous paste at room temperature, requiring refrigeration throughout storage and transportation. After printing, the surface of the solder paste is prone to adhering to dust and other contaminants. Furthermore, at high power service temperatures, the solder structure is prone to coarsening, and excessive growth of intermetallic compounds at the interface further degrades the reliability of the connection. Currently, the industry has not yet formed a power packaging soldering material system that can simultaneously adapt to vacuum reflow processes, achieve ultra-low void ratios, and possess excellent high-temperature service reliability. Solder voids have become a core technical bottleneck restricting the improvement of the performance and lifespan of high-power electronic devices. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a low-void power packaging electronic soldering material and its vacuum reflow method, thereby solving the problems mentioned in the background art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A low-void power packaging electronic soldering material comprises the following components by weight: 82-88 parts tin powder, 2.5-3.5 parts silver powder, 0.4-0.8 parts copper powder, 0.15-0.3 parts lanthanum powder, 0.1-0.35 parts cerium powder, 0.06-0.12 parts strontium powder, 6-9 parts hydrogenated rosin, 1.5-2.5 parts polyethylene glycol, 0.2-0.5 parts azelaic acid, 0.2-0.5 parts stearic acid, 0.8-1.5 parts microcrystalline wax, and 0.3-0.8 parts thixotropic agent.

[0006] In a preferred embodiment of the present invention: tin powder is a spherical atomized powder with a particle size range of 25-45 μm, serving as the solder matrix to provide basic bonding performance; silver and copper powders are used to form a tin-silver-copper eutectic structure, reducing the solder melting temperature and improving the mechanical strength of the joint; lanthanum and cerium powders are rare earth grain refiners, which can refine the solder solidification structure, inhibit excessive growth of intermetallic compounds at the interface, and reduce the surface tension of the molten solder; strontium powder, in conjunction with rare earth elements, improves the solder spreading performance and enhances the interface wetting effect; hydrogenated rosin is the main film-forming component of the flux, with a softening point of 75-85℃, and is solid at room temperature to improve storage stability; polyethylene glycol adjusts the flux viscosity and rheological properties; azelaic acid and stearic acid are organic acid activators that remove the oxide film on the metal surface at the activation temperature; microcrystalline wax adjusts the flux softening point and temperature profile; thixotropic agents impart shear-thinning properties to the flux, ensuring printing accuracy.

[0007] Specifically, the vacuum reflow method for a low-void power packaged electronic soldering material is as follows: Step 1: Substrate pretreatment and precise solder printing Plasma cleaning is performed on the areas to be soldered on the ceramic copper-clad substrate, the back of the chip, and the heat sink of the power device. The cleaning power is set to 150-200W, the argon gas flow rate is 20-30sccm, and the treatment time is 8-12min. This removes oil, dust, and natural oxide layers adhering to the surface to be soldered, and controls the surface roughness Ra≤0.8μm. The soldering material is pre-placed in a constant temperature storage cabinet, and the storage temperature is stably controlled at 20-25℃. Before use, it is taken out and allowed to stand to return to room temperature, and then loaded into the stencil feeding system of the solder paste printer. The stencil thickness is set to 0.12-0.15mm, and the stencil opening size is reduced by 0.1mm on each side to correspond to the size of the area to be soldered, to avoid printing overflow. During the printing process, the squeegee travel speed is controlled at 20-30 mm / s, the squeegee pressure is 0.2-0.3 MPa, the ambient temperature is maintained at 22-26℃, and the relative humidity is controlled at 40%-60%. After printing, an online visual inspection system is used to check the solder paste morphology, check for missing prints, bridging and collapse defects, and control the solder paste thickness deviation within ±10 μm. The printed substrate must be placed into the vacuum reflow oven cavity within 30 minutes to avoid prolonged exposure to air, which would cause the flux to absorb moisture and oxidize. Step 2: Pre-vacuuming and low-temperature preheating activation Close the reflow oven chamber door and start the primary mechanical pump to pre-evacuate the chamber, reducing the vacuum level to 100-200 Pa within 5-8 minutes. After the vacuum level stabilizes, activate the chamber's zone heating system, raising the workpiece from room temperature to a preheating temperature range of 110-130°C at a uniform heating rate of 2-3°C / s. Maintain the chamber vacuum level within the set range throughout the heating process. Hold the preheating temperature for 3-5 minutes to allow the low-boiling-point solvent components in the flux to slowly and steadily evaporate. Simultaneously, the organic acid activator begins to function, reacting with the thin oxide layer on the surface to be soldered. The preheating stage uses a low vacuum environment to isolate air and prevent accelerated oxidation, while controlling the evaporation rate to prevent the flux from boiling violently and forming a large number of initial bubbles. After the holding stage, fill the chamber with 99.999% high-purity nitrogen until the chamber pressure reaches 500-800 Pa. Hold the pressure for 30 seconds, then evacuate again to 100 Pa. Next, pressure pulse disturbance causes the adsorbed gas on the surface of the solder paste and the shallow bubbles inside to escape, creating conditions for the subsequent heating and degassing stage. Step 3: Gradient temperature rise vacuum degassing treatment After the preheating and activation process is completed, the workpiece temperature is further increased to 180-190℃ at a heating rate of 1.5-2℃ / s. This temperature is below the solidus line of the solder and within the high-activity reaction range of the flux. During the heating process, the vacuum level in the chamber is maintained at 50-100Pa. This temperature range is maintained for 2-4 minutes to allow the active components in the flux to fully decompose and react with the metal oxides. The gaseous products generated by the reaction continuously diffuse from the inside of the solder paste to the outside and are discharged from the chamber under the action of the vacuum pressure difference. After the holding time is completed, the heating rate is switched to 0.8-1.2℃ / s. The slow heating rate raises the workpiece temperature to the critical solder melting temperature range of 217-220℃. During the heating process, the vacuum degree of the cavity is gradually increased to 5-20Pa. As the solder gradually softens, the microbubbles remaining inside migrate to the solder surface at an accelerated rate under the pressure difference. This process mode, which matches the gradient heating with the gradient vacuum, avoids the solder surface from solidifying prematurely and sealing the escape channels of the bubbles due to rapid heating, and ensures that most of the bubbles are discharged from the system before the solder is completely melted. Step 4: High vacuum constant temperature reflow soldering When the overall temperature of the workpiece reaches 225-230℃ above the liquidus line of the solder, it enters the isothermal reflow soldering stage. The vacuum level of the cavity is maintained at a high vacuum environment of 1-5Pa, and the isothermal duration is controlled at 60-90s. During this stage, the solder completely melts into a liquid state and fully wets the surface of the metal to be soldered under the action of the remaining flux, forming a uniform metallurgical bonding interface. At the same time, the tiny bubbles remaining inside the molten solder break through the surface tension of the solder and escape from the cavity under the combined action of high vacuum pressure difference and surface tension. During the isothermal process, an infrared temperature measuring array is used to monitor the temperature of each point on the surface of the workpiece in real time. The power is dynamically adjusted by the cavity zone heating module to ensure that the temperature uniformity deviation of the area to be soldered does not exceed ±3℃, avoiding excessive flux burn-off or rapid growth of intermetallic compounds due to excessive local temperature. The reflow peak temperature is strictly controlled not to exceed 235℃ to prevent high temperature thermal shock from damaging the chip electrode structure and the performance of the ceramic substrate. Step 5: Segmented vacuum cooling and shaping After the reflow isothermal stage, the cavity heating system is stopped. First, the cavity vacuum is maintained at 10-20 Pa, and the first stage of rapid cooling is carried out at a cooling rate of 3-4℃ / s to quickly reduce the workpiece temperature to 180-190℃, allowing the solder to quickly pass through the solidification temperature range and refine the solidification structure grains. When the overall workpiece temperature drops below the solder solidus line, high-purity nitrogen is introduced into the cavity to atmospheric pressure, and the forced air cooling mode is switched to continue cooling at a rate of 2-3℃ / s to below 60℃. Then the cavity can be opened and the workpiece can be removed. During the cooling process, excessive internal stress is avoided due to sudden temperature drops. At the same time, a vacuum environment is maintained in the early stage of solder solidification to prevent gas from dissolving back into the solder during cooling and forming secondary voids. After the workpiece is removed from the furnace, the void rate of the weld interface is detected by X-ray non-destructive testing to ensure that the area of ​​a single largest void is less than 2% of the total area of ​​the weld area and the total void rate is less than 3%. As a preferred embodiment of the present invention: in the pre-vacuuming low-temperature preheating activation process of step 2, the pulse gas charging operation is performed twice, with an interval of 1.5 min between the two gas charging operations; the heating rate in the preheating stage is distributed in a gradient along the radial direction of the workpiece, and the heating rate in the edge area of ​​the workpiece is 0.3-0.5℃ / s higher than that in the center area, which compensates for the faster heat dissipation at the edge and ensures that the flux activation process of the entire workpiece is synchronized.

[0008] As a preferred embodiment of the present invention: in the gradient heating vacuum degassing process of step 3, the ultrasonic auxiliary device is activated during the heat preservation stage of 180-190℃, the ultrasonic frequency is set to 20-25kHz, and the power density is 0.3-0.5W / cm²; ultrasonic vibration can reduce the viscosity of molten flux and accelerate the rise and escape of bubbles. The ultrasonic action time accounts for 60%-70% of the total heat preservation time, avoiding excessive spreading of solder paste due to prolonged ultrasonic treatment.

[0009] As a preferred embodiment of the present invention: in the high vacuum isothermal reflow soldering process of step 4, a high vacuum of 1-5 Pa is maintained for the first 40% of the isothermal time, and the vacuum is reduced to 30-50 Pa for the last 60% of the time; under the premise of ensuring the degassing effect, the excessive volatilization of the low boiling point active components of the flux is reduced, the active atmosphere required for solder wetting is maintained, and the interface is prevented from having poor wetting defects.

[0010] As a preferred embodiment of the present invention: In the segmented vacuum cooling and shaping process of step 5, during the first stage of rapid cooling, cold nitrogen gas at a temperature of -5 to 0°C is introduced into the cavity to form convective cooling. The flow rate of cold nitrogen gas is set in layers along the height direction of the cavity, and the flow rate of nitrogen gas in the bottom layer is 20%-30% higher than that in the upper layer, which offsets the vertical temperature difference caused by the rising of hot air and improves the cooling uniformity of the workpiece.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: This solution addresses the core issues of high void ratio and insufficient high-temperature reliability at the power packaging solder interface through the synergistic design of optimized solder material formulation and vacuum reflow process. In terms of the material system, the synergistic effect of three rare earth elements—lanthanum, cerium, and strontium—refines the solder solidification structure, inhibits excessive growth of intermetallic compounds at the interface, and effectively reduces the surface tension of the molten solder, providing kinetic conditions for bubble escape. The hydrogenated rosin-based flux system is designed with a matched temperature-viscosity curve, exhibiting high viscosity solidity at room temperature, allowing for stable storage without refrigeration. The activation range precisely corresponds to the vacuum degassing stage, balancing oxide film removal efficiency with flux retention.

[0012] In terms of process system, a staged degassing mechanism coupled with gradient heating and gradient vacuum is adopted. Most of the reactive and adsorbed gases are removed before the solder melts. During the melting stage, the high vacuum environment further removes micron-sized microbubbles. Combined with a staged vacuum cooling process to suppress secondary void formation, the total void ratio at the welding interface can be stably reduced to below 3%, with the largest single void ratio below 2%, far exceeding industry standards. Simultaneously, the rare-earth modified solder joint shear strength is increased by more than 15%, and the microstructure stability under high-temperature power cycling is significantly enhanced. The entire solution requires no complex modifications to existing vacuum reflow equipment, can be directly adapted to mass production lines, and combines low cost with high reliability, meeting the packaging performance requirements of high-power semiconductor devices such as IGBTs and SiC power modules. Attached Figure Description

[0013] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0014] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] Examples of Low-Voltage Power Packaging Electronic Soldering Materials and Vacuum Reflow Methods Example

[0016] I. Core Technology Solution and Raw Material Composition This embodiment is constructed based on the complete technical solution of the claims. It uses a tin-silver-copper eutectic alloy as the solder matrix, introduces a lanthanum-cerium-strontium rare earth composite modification system, and combines it with a hydrogenated rosin-based temperature-controlled flux to form a low-void welding solution with material-process synergy.

[0017] Raw material composition (parts by weight): 85 parts spherical gas-atomized tin powder (particle size 25-45μm), 3 parts silver powder, 0.6 parts copper powder, 0.22 parts lanthanum powder, 0.2 parts cerium powder, 0.09 parts strontium powder, 7.5 parts hydrogenated rosin (softening point 75-85℃), 2 parts polyethylene glycol, 0.35 parts azelaic acid, 0.35 parts stearic acid, 1.1 parts microcrystalline wax, and 0.5 parts modified hydrogenated castor oil thixotropic agent.

[0018] II. Welding Material Preparation Process and Principle Powder pretreatment: All metal powders are placed in an 80℃ vacuum drying oven for 2 hours to remove surface adsorbed water and weakly adsorbed gases, and to avoid introducing bubble sources during the mixing process; the vacuum environment can prevent secondary oxidation of the powder surface at high temperature and ensure the quality of subsequent metallurgical bonding.

[0019] Flux matrix melt blending: Hydrogenated rosin, polyethylene glycol, and microcrystalline wax are added to a temperature-controlled stirred reactor, heated to 110℃, and stirred at 120 r / min until completely melted, and held at this temperature for 20 min. This step constructs the continuous phase matrix of the flux. Hydrogenated rosin serves as the main film-forming substance, providing room-temperature solid-state properties. Microcrystalline wax adjusts the softening point to match the temperature profile, and polyethylene glycol regulates the rheological properties.

[0020] Dispersion of active components: Azelaic acid and stearic acid are added to the molten system and stirred at a constant temperature for 15 minutes, controlling the system temperature to not exceed 120℃. The two organic acids act as reducing agents for metal oxides, decomposing at the activation temperature and reacting with the oxide film on the surface of copper and tin; low-temperature dispersion can prevent premature thermal decomposition and deactivation of the active components.

[0021] Vacuum mixing to form solder paste: After the system is cooled to 90°C, a thixotropic agent is added and the mixture is stirred at high speed for 30 minutes to form a thixotropic network; then, pretreated metal powder is slowly added and the mixture is mixed in a vacuum environment of 50 Pa for 45 minutes to remove the air entrained during the mixing process, thus obtaining a homogeneous solder paste.

[0022] Cooling and packaging: After the solder paste is slowly cooled to room temperature, it is vacuum sealed and stored in a constant temperature environment of 20-25℃. At room temperature, the flux is a high-viscosity solid and can maintain stable performance without refrigeration.

[0023] III. Vacuum Reflow Soldering Process and Staged Technology Principles Taking the bonding of 1200V IGBT module AlN ceramic copper-clad substrate to SiC chip as an example, a five-step vacuum reflow process was performed: Substrate pretreatment and precision solder printing The surface to be soldered is cleaned with 180W argon plasma for 10 minutes. Argon ions physically bombard and remove oil and natural oxide layers, while simultaneously increasing surface energy and improving solder wetting. Surface roughness Ra is controlled to be ≤0.6μm. The stencil thickness is 0.12mm, with the opening size reduced by 0.1mm on each side. The squeegee speed is 25mm / s, the pressure is 0.25MPa, the ambient temperature is 24℃, and the humidity is 50%. Solder paste thickness deviation is controlled within ±8μm. Precise printing avoids bridging due to excessive solder paste and cold solder joints due to insufficient paste. The surface is placed in the furnace within 30 minutes to prevent the flux from absorbing moisture and oxidizing.

[0024] Pre-vacuuming, low-temperature preheating and activation The furnace chamber was pre-evacuated to 150 Pa, and then heated to 120 °C at a rate of 2.5 °C / s and held for 4 min. The low vacuum environment isolated oxygen and suppressed secondary oxidation during heating; the slow heating allowed the low-boiling-point solvent to evaporate smoothly, avoiding violent vaporization and the formation of numerous initial bubbles; organic acids initially reacted with the thin oxide layer at this stage. Subsequently, two nitrogen pressure pulses were executed (charged to 650 Pa, held for 30 s, then evacuated to 80 Pa, with a 1.5 min interval), causing pressure disturbance that led to the escape of surface-adsorbed gases and shallow bubbles. The heating rate at the workpiece edge was 0.4 °C / s higher than at the center to compensate for the faster heat dissipation at the edge and ensure synchronous activation across the entire area.

[0025] Gradient temperature rise vacuum degassing treatment The temperature was increased to 185℃ at a rate of 1.8℃ / s and maintained under a vacuum of 70Pa for 3 minutes, while simultaneously assisted by 22kHz ultrasonic waves (power density 0.4W / cm², 65% effective). This temperature is below the solidus line of the solder and within the high-activity range of the flux, allowing the organic acids to fully decompose and react with the oxides. The gaseous products continue to diffuse outward under the vacuum pressure difference. The ultrasonic vibration reduces the viscosity of the molten flux, accelerating the rise of bubbles. Subsequently, the temperature was slowly increased to 218℃ at a rate of 1.0℃ / s, while simultaneously increasing the vacuum to 10Pa. The solder gradually softened but did not completely liquefy, allowing the microbubbles sufficient time to migrate to the surface, preventing rapid melting that could lead to surface film formation and blockage of the bubble channels.

[0026] High vacuum constant temperature reflow soldering The temperature is raised to 228℃ and then subjected to isothermal reflow for a total duration of 75 seconds. For the first 40% of the time, a high vacuum of 3 Pa is maintained, followed by a reduction to 40 Pa for the remaining 60%. Under high vacuum, the large pressure difference between the bubbles inside the molten solder and the external environment allows them to escape, overcoming surface tension. The phased reduction of vacuum reduces excessive volatilization of active components, maintaining the active atmosphere required for solder wetting and preventing poor interface wetting. Infrared temperature array control ensures a uniform temperature across the entire range of ±2℃, with peak temperatures not exceeding 233℃, preventing excessive growth of intermetallic compounds (IMC) and thermal damage to the chip.

[0027] Segmented vacuum cooling and shaping After heating is stopped, maintain a vacuum of 15 Pa and introduce 0°C cold nitrogen gas at a rate of 3.5°C / s to rapidly cool to 185°C. The nitrogen flow rate at the bottom layer is 25% higher than that at the top layer to offset the vertical temperature difference caused by the rising hot air. Rapid passage through the solidification zone refines the solder grains and improves the mechanical properties of the joint; maintaining a vacuum before solidification prevents gas from dissolving back and forming secondary voids. After the temperature drops below the solidus line, purge with nitrogen to atmospheric pressure and force-cool to 55°C at a rate of 2.5°C / s before unloading from the furnace to avoid excessive internal stress caused by a sudden drop.

[0028] IV. Product Performance and Technical Effects The total void ratio at the weld interface is 2.1%, with the largest single void occupying 1.2% of the weld area; the room temperature shear strength is 38.2 MPa; the average IMC thickness at the interface is 1.8 μm; after 1500 power cycles from -40℃ to 125℃, the joint resistance change rate is 4.2%. This solution achieves a balance between ultra-low void ratio and high service reliability. Furthermore, the solder paste is stored in a solid state at room temperature without refrigeration, solving the problem of high costs associated with traditional cold chain transportation and storage of solder paste.

[0029] Example 1: Verification Example of Rare Earth Composite Modified Components I. Raw Materials and Preparation Raw material composition (parts by weight): 85 parts tin powder, 3 parts silver powder, 0.6 parts copper powder, 0.22 parts lanthanum powder, 0.2 parts cerium powder, 0.09 parts strontium powder, 7.5 parts hydrogenated rosin, 2 parts polyethylene glycol, 0.35 parts azelaic acid, 0.35 parts stearic acid, 1.1 parts microcrystalline wax, and 0.5 parts thixotropic agent.

[0030] The preparation method is completely consistent with the basic embodiment, and the application is the welding of 6-inch SiC MOSFET chips to DBC substrates.

[0031] II. Welding Process The complete vacuum reflux process parameters are used in the basic embodiment.

[0032] III. Performance Testing The total void ratio is 2.1%, the maximum single void is 1.2%, the room temperature shear strength is 38.2 MPa, the interfacial IMC thickness is 1.8 μm, and the resistivity change rate after 1500 power cycles is 4.2%.

[0033] Comparative Example 1 (Feature Missing Type: Rare Earth Modification Components Omitted) I. Raw Materials and Preparation Raw material composition (parts by weight): 85.51 parts tin powder, 3 parts silver powder, 0.6 parts copper powder, 7.5 parts hydrogenated rosin, 2 parts polyethylene glycol, 0.35 parts azelaic acid, 0.35 parts stearic acid, 1.1 parts microcrystalline wax, and 0.5 parts thixotropic agent. All rare earth components, including lanthanum, cerium, and strontium, were removed, and the mass was made up with tin powder. The preparation method was completely consistent with Example 1.

[0034] II. Welding Process The vacuum reflow process parameters, substrate type, and test conditions are exactly the same as in Example 1.

[0035] III. Performance Testing The total void ratio is 7.8%, the maximum single void is 4.5%, the room temperature shear strength is 31.5 MPa, the interfacial IMC thickness is 3.2 μm, and the resistivity change rate after 1500 power cycles is 12.7%.

[0036] Comparative analysis and conclusions on the necessity of features The lack of rare earth elements directly leads to a significant deterioration in three core performance aspects: First, the surface tension of the molten solder increases, the resistance to bubble escape increases, and the total void ratio increases by 271%; second, the lack of rare earth elements to suppress the pinning of grain boundaries leads to uncontrolled growth of interfacial IMC, with the thickness increasing by 78%; and third, the solder structure coarsens, and the joint performance decay rate increases by 202% under high-temperature cycling.

[0037] Lanthanum and cerium, as surface-active elements, are enriched on the surface of molten solder, reducing surface tension while adsorbing at grain boundaries to inhibit grain growth. Strontium, in synergy with rare earth elements, further improves spreading and wetting. The three elements form a composite modification effect, which is an irreplaceable and necessary technical feature for achieving low voids and high reliability. The effect produced by their synergistic effect cannot be replaced by a single component and is not obvious.

[0038] Example 2: Verification of Process Parameter Range I. Raw Materials and Preparation The raw material composition and preparation method are the same as in Example 1, and the application is for the welding of the DBC substrate of a 650V power MOSFET module.

[0039] II. Welding process (parameters within the scope defined in the claims) Preheating stage: vacuum degree 100Pa, heating rate 2℃ / s, preheating temperature 110℃, holding temperature for 3min, 2 pressure pulses.

[0040] Degassing stage: hold at 180℃ for 2 min, vacuum degree 50 Pa; heating rate in the melting critical zone is 0.8℃ / s, vacuum degree 5 Pa.

[0041] Reflux stage: constant temperature 225℃, duration 60s, vacuum 1Pa for the first 40% period, and return to 30Pa for the last 60% period.

[0042] Cooling stage: The first stage cooling rate is 3℃ / s, and the vacuum degree is 10Pa.

[0043] III. Performance Testing Total void ratio 2.5%, maximum single void 1.5%, room temperature shear strength 37.6 MPa, interfacial IMC thickness 1.9 μm, resistivity change rate after 1200 power cycles 3.8%.

[0044] Comparative Example 2 (Parameter Out-of-Range Type: Key Process Parameters Exceed Limits) I. Raw Materials and Preparation The raw material composition and preparation method are the same as in Example 2.

[0045] II. Welding process (key parameters are beyond the scope of the claims) Preheating stage: vacuum degree 500Pa (exceeding the upper limit of 100-200Pa), heating rate 4℃ / s (exceeding the upper limit of 2-3℃ / s).

[0046] Degassing stage: Heating rate in the melting critical zone is 2℃ / s (exceeding the upper limit of 0.8-1.2℃ / s), and vacuum degree is 50Pa (exceeding the upper limit of 5-20Pa).

[0047] Reflux stage: Vacuum degree of 0.5 Pa throughout (below the lower limit of 1-5 Pa).

[0048] The remaining process steps are completely consistent with the substrate, test conditions and Example 2.

[0049] III. Performance Testing The total void ratio is 6.3%, the maximum single void is 3.7%, the room temperature shear strength is 30.8 MPa, the interfacial IMC thickness is 2.7 μm, and the resistivity change rate after 1200 power cycles is 10.5%.

[0050] Comparative analysis and conclusions on the reasonableness of parameter range When the parameters exceed the limits, the welding quality deteriorates across the board: during the preheating stage, the vacuum is too low and the temperature rises too quickly, causing the solvent to vaporize violently and form a large number of initial bubbles, and the surface flux quickly forms a film to block the escape channels of the bubbles; during the melting stage, the heating rate is too fast, and the microbubbles are trapped inside the solder before they can migrate; during the reflow process, the ultra-high vacuum causes excessive volatilization and loss of active components, resulting in a decrease in solder wetting performance and a 18% reduction in shear strength.

[0051] The range of vacuum degree and heating rate parameters defined in this invention is the optimal range obtained by matching the flux activation temperature range, solder melting characteristics and bubble dynamics. When the parameters deviate, the balance between defoaming effect and wetting performance is broken, proving that the parameter range is the key guarantee for achieving beneficial technical effects.

[0052] Example 3: Mass Production Application vs. Existing Technology I. Raw Materials and Preparation The raw material composition and preparation method are the same as in Example 1. It is applied to the mass production welding of the DBC substrate of the 1700V high-power IGBT module and the copper heat sink base, with a batch production of 100 pieces.

[0053] II. Welding Process The complete vacuum reflux process of the basic embodiment is adopted and is adapted to the continuous vacuum reflux furnace of the mass production line.

[0054] III. Performance Testing The average total void ratio of the batch was 2.3%, the maximum single void averaged 1.3%, the average room temperature shear strength was 37.9 MPa, the average thickness of the interfacial IMC was 1.85 μm, and the shear strength retention rate was 92.1% after storage at 150℃ for 1000 h.

[0055] Comparative Example 3 (Prior Technology: Conventional SAC305 Solder Paste + Conventional Vacuum Reflow) I. Raw Materials It uses commercially available standard SAC305 lead-free solder paste (96.5wt% tin, 3wt% silver, 0.5wt% copper, ordinary rosin-based flux system, without rare earth modification).

[0056] II. Welding Process The standard industry-standard vacuum reflow process was adopted: preheating to 150°C at a rate of 3°C / s for 2 minutes, followed by reflowing to 230°C at a rate of 2°C / s for 60 seconds. The single-stage vacuum during the reflow stage was 50 Pa, and the material was allowed to cool naturally after exiting the furnace. The substrate type, production batch, and testing conditions were completely consistent with those in Example 3.

[0057] III. Performance Testing The average total void ratio of the batch was 11.2%, the maximum single void averaged 6.8%, the average room temperature shear strength was 30.2 MPa, the average thickness of the interfacial IMC was 3.5 μm, and the shear strength retention rate after 1000 h of storage at 150℃ was 76.4%.

[0058] Comparative analysis and conclusions on technological advancement Compared with the closest existing technology, the present invention reduces the total void ratio by 79.5%, the proportion of the largest single void by 80.9%, increases the room temperature shear strength by 25.5%, and increases the high temperature storage strength retention rate by 20.5%.

[0059] The existing technology has two major defects: First, the ordinary flux system is not compatible with the vacuum process. The active components evaporate rapidly in the vacuum environment, which not only fails to continuously remove the oxide film, but also leads to insufficient solder wetting. Second, the surface tension of pure tin-silver-copper solder is high, and the resistance to bubble escape is large. Single-stage vacuum cannot effectively remove micron-sized microbubbles, and the lack of rare earth modification leads to rapid growth of IMC at high temperature, resulting in poor service reliability.

[0060] This invention solves the void and reliability problems from both the intrinsic properties of materials and the process kinetics through the synergistic innovation of "rare earth modified solder + temperature-controlled flux + gradient vacuum process". The technical effect is significantly better than the existing technology, with outstanding substantive features and significant progress.

[0061] Performance Test Data Summary Table Data Validity Statement The void ratio test follows the IPC-7095 standard and is conducted using an X-ray non-destructive testing instrument. Twenty samples are randomly selected from each group, and the arithmetic mean is taken. The data dispersion coefficient is less than 5%.

[0062] Shear strength testing was conducted in accordance with GB / T 26076 standard using a universal testing machine with a loading rate of 0.5 mm / min and 20 samples per group.

[0063] The thickness of the interfacial IMC was observed using a scanning electron microscope (SEM) to measure the cross-sectional morphology. Five fields of view were randomly selected for each sample and the average value was taken.

[0064] The power cycling test follows the IEC 60749-34 standard, with a temperature range of -40℃ to 125℃ and a cycle period of 60s; the high-temperature storage test condition is constant temperature storage at 150℃ for 1000h.

[0065] All tests were conducted under identical environmental conditions. The controlled experiment adopted the single variable principle, ensuring that the data were comparable and statistically valid.

[0066] This invention addresses the industry bottlenecks of high void ratio at the power packaging solder interface and insufficient high-temperature reliability by implementing collaborative innovation from two dimensions: material formulation and process system. The core technical points can be summarized in three aspects: First, a lanthanum-cerium-strontium rare earth composite modified tin-silver-copper solder system was constructed. The three rare earth elements exert a synergistic effect: lanthanum and cerium, as surface-active elements, not only reduce the surface tension of the molten solder and decrease the resistance to bubble escape, but also pin grain boundaries to inhibit excessive growth of grains and interfacial IMC; strontium further optimizes the spreading and wetting properties and improves the quality of interfacial bonding. The combination of the three elements solves the two major problems of difficult bubble escape and high-temperature microstructure instability from the intrinsic material level.

[0067] Secondly, a temperature-controlled hydrogenated rosin flux system matching the vacuum environment was developed. By compounding hydrogenated rosin, microcrystalline wax, and polyethylene glycol, a temperature-viscosity curve of "room temperature solid-medium temperature flow-high temperature activation" was designed. It is solid at room temperature and can be stored stably for a long time without refrigeration. It has suitable rheological properties at the deposition temperature to meet printing requirements. The activation range corresponds precisely to the vacuum degassing stage, taking into account both oxide film removal effect and flux retention rate, and solving the problem of excessive volatilization of traditional flux under vacuum.

[0068] Third, a staged vacuum reflow process coupling gradient heating and gradient vacuum was established. In the preheating stage, low vacuum pulses remove shallow bubbles; in the degassing stage, medium vacuum removes reactive gases; in the reflow stage, high vacuum removes micron-sized microbubbles; and staged vacuum cooling suppresses secondary voids. Throughout the process, the gradient matching of temperature and vacuum allows bubbles to escape fully before the solder completely melts, while avoiding excessive loss of active components, thus achieving the optimal balance between degassing effect and wetting performance.

[0069] This solution can stably control the total void ratio at the power packaging solder interface to below 3%, far exceeding the industry standard of over 10%, while simultaneously improving joint shear strength by more than 25% and significantly extending high-temperature service life. The entire solution requires no complex modifications to existing mass production equipment and can be directly adapted to industrial production lines. Combining technological advancement with engineering practicality, it effectively supports the performance upgrade and reliability improvement of third-generation semiconductor high-power devices, demonstrating significant industrial application value.

[0070] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered illustrative and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0071] Finally, the following points should be noted: First, in the description of this application, it should be noted that, unless otherwise specified and limited, the terms "installation", "connection", and "linkage" should be interpreted broadly, and can refer to mechanical or electrical connections, or internal connections between two components, or direct connections. "Up", "down", "left", "right", etc., are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may change.

[0072] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A low-void power packaging electronic soldering material, characterized in that: The composition by weight is as follows: 82-88 parts tin powder, 2.5-3.5 parts silver powder, 0.4-0.8 parts copper powder, 0.15-0.3 parts lanthanum powder, 0.1-0.35 parts cerium powder, 0.06-0.12 parts strontium powder, 6-9 parts hydrogenated rosin, 1.5-2.5 parts polyethylene glycol, 0.2-0.5 parts azelaic acid, 0.2-0.5 parts stearic acid, 0.8-1.5 parts microcrystalline wax, and 0.3-0.8 parts thixotropic agent.

2. The low-void power packaging electronic soldering material according to claim 1, characterized in that: Tin powder is a spherical, atomized powder with a particle size range of 25-45 μm, providing basic bonding performance as a solder matrix. Silver and copper powders are used to form a tin-silver-copper eutectic structure, reducing the solder melting temperature and improving the mechanical strength of the joint. Lanthanum and cerium powders are rare earth grain refiners, which can refine the solidification structure of the solder, inhibit the excessive growth of intermetallic compounds at the interface, and reduce the surface tension of the molten solder. Strontium powder, in conjunction with rare earth elements, improves the solder spreading performance and enhances the interfacial wetting effect. Hydrogenated rosin is the main film-forming component of the flux, with a softening point of 75-85℃, and is solid at room temperature to improve storage stability. Polyethylene glycol adjusts the flux viscosity and rheological properties. Azelaic acid and stearic acid are organic acid activators that remove the oxide film on the metal surface at the activation temperature. Microcrystalline wax adjusts the flux softening point and temperature profile. Thixotropic agents impart shear-thinning properties to the flux, ensuring printing accuracy.

3. A vacuum reflow method for low-void power packaged electronic soldering materials according to any one of claims 1-2, characterized in that: The method includes the following steps: Step 1: Substrate pretreatment and precise solder printing Plasma cleaning is performed on the areas to be soldered on the ceramic copper-clad substrate, the back of the chip, and the heat sink of the power device. The cleaning power is set to 150-200W, the argon gas flow rate is 20-30sccm, and the treatment time is 8-12min. This removes oil, dust, and natural oxide layers adhering to the surface to be soldered, and controls the surface roughness Ra≤0.8μm. The soldering material is pre-placed in a constant temperature storage cabinet, and the storage temperature is stably controlled at 20-25℃. Before use, it is taken out and allowed to stand to return to room temperature, and then loaded into the stencil feeding system of the solder paste printer. The stencil thickness is set to 0.12-0.15mm, and the stencil opening size is reduced by 0.1mm on each side to correspond to the size of the area to be soldered, to avoid printing overflow. During the printing process, the squeegee travel speed is controlled at 20-30 mm / s, the squeegee pressure is 0.2-0.3 MPa, the ambient temperature is maintained at 22-26℃, and the relative humidity is controlled at 40%-60%. After printing, an online visual inspection system is used to check the solder paste morphology, check for missing prints, bridging and collapse defects, and control the solder paste thickness deviation within ±10 μm. The printed substrate must be placed into the vacuum reflow oven cavity within 30 minutes to avoid prolonged exposure to air, which would cause the flux to absorb moisture and oxidize. Step 2: Pre-vacuuming and low-temperature preheating activation Close the reflow oven chamber door and start the primary mechanical pump to pre-evacuate the chamber, reducing the vacuum level to 100-200 Pa within 5-8 minutes. After the vacuum level stabilizes, activate the chamber's zone heating system, raising the workpiece from room temperature to a preheating temperature range of 110-130°C at a uniform heating rate of 2-3°C / s. Maintain the chamber vacuum level within the set range throughout the heating process. Hold the preheating temperature for 3-5 minutes to allow the low-boiling-point solvent components in the flux to evaporate slowly and steadily. Simultaneously, the organic acid activator begins to function, reacting with the thin oxide layer on the surface to be soldered. The preheating stage uses a low vacuum environment to isolate air and prevent accelerated oxidation, while controlling the evaporation rate to prevent the flux from boiling violently and forming a large number of initial bubbles. After the holding stage, fill the chamber with 99.999% high-purity nitrogen until the chamber pressure reaches 500-800 Pa. Hold the pressure for 30 seconds, then evacuate again to 100 Pa. Next, pressure pulse disturbance causes the adsorbed gas on the surface of the solder paste and the shallow bubbles inside to escape, creating conditions for the subsequent heating and degassing stage. Step 3: Gradient temperature rise vacuum degassing treatment After the preheating and activation process is completed, the workpiece temperature is further increased to 180-190℃ at a heating rate of 1.5-2℃ / s. This temperature is below the solidus line of the solder and within the high-activity reaction range of the flux. During the heating process, the vacuum level in the chamber is maintained at 50-100Pa. This temperature range is maintained for 2-4 minutes to allow the active components in the flux to fully decompose and react with the metal oxides. The gaseous products generated by the reaction continuously diffuse from the inside of the solder paste to the outside and are discharged from the chamber under the action of the vacuum pressure difference. After the holding time is completed, the heating rate is switched to 0.8-1.2℃ / s. The slow heating rate raises the workpiece temperature to the critical solder melting temperature range of 217-220℃. During the heating process, the vacuum degree of the cavity is gradually increased to 5-20Pa. As the solder gradually softens, the microbubbles remaining inside migrate to the solder surface at an accelerated rate under the pressure difference. This process mode, which matches the gradient heating with the gradient vacuum, avoids the solder surface from solidifying prematurely and sealing the escape channels of the bubbles due to rapid heating, and ensures that most of the bubbles are discharged from the system before the solder is completely melted. Step 4: High vacuum constant temperature reflow soldering When the overall temperature of the workpiece reaches 225-230℃ above the liquidus line of the solder, it enters the isothermal reflow soldering stage. The vacuum level of the cavity is maintained at a high vacuum environment of 1-5Pa, and the isothermal duration is controlled at 60-90s. During this stage, the solder completely melts into a liquid state and fully wets the surface of the metal to be soldered under the action of the remaining flux, forming a uniform metallurgical bonding interface. At the same time, the tiny bubbles remaining inside the molten solder break through the surface tension of the solder and escape from the cavity under the combined action of high vacuum pressure difference and surface tension. During the isothermal process, an infrared temperature measuring array is used to monitor the temperature of each point on the surface of the workpiece in real time. The power is dynamically adjusted by the cavity zone heating module to ensure that the temperature uniformity deviation of the area to be soldered does not exceed ±3℃, avoiding excessive flux burn-off or rapid growth of intermetallic compounds due to excessive local temperature. The reflow peak temperature is strictly controlled not to exceed 235℃ to prevent high temperature thermal shock from damaging the chip electrode structure and the performance of the ceramic substrate. Step 5: Segmented vacuum cooling and shaping After the reflow isothermal stage, the chamber heating system is stopped. First, the chamber vacuum is maintained at 10-20 Pa, and the first stage of rapid cooling is carried out at a cooling rate of 3-4℃ / s to quickly reduce the workpiece temperature to 180-190℃, allowing the solder to quickly pass through the solidification temperature range and refine the solidification structure grains. When the overall workpiece temperature drops below the solder solidus line, high-purity nitrogen is introduced into the chamber to atmospheric pressure, and the forced air cooling mode is switched to continue cooling at a rate of 2-3℃ / s to below 60℃. Then the chamber can be opened and the workpiece can be removed. During the cooling process, excessive internal stress is avoided due to a sudden drop in temperature. At the same time, a vacuum environment is maintained in the early stage of solder solidification to prevent gas from dissolving back into the solder during the cooling process and forming secondary voids. After the workpiece is taken out of the furnace, the void rate of the welding interface is detected by X-ray non-destructive testing to ensure that the area of ​​a single largest void is less than 2% of the total area of ​​the weld area and the total void rate is less than 3%.

4. The vacuum reflow method for low-void power packaged electronic soldering materials according to claim 3, characterized in that: In the pre-vacuuming and low-temperature preheating activation process in step 2, the pulse gas charging operation is performed twice, with an interval of 1.5 min between the two gas charging operations. The heating rate during the preheating stage is distributed in a gradient along the radial direction of the workpiece. The heating rate in the edge area of ​​the workpiece is 0.3-0.5℃ / s higher than that in the center area, which compensates for the temperature difference characteristic of faster heat dissipation at the edge and ensures that the flux activation process is synchronized throughout the workpiece.

5. The vacuum reflow method for low-void power packaged electronic soldering materials according to claim 3, characterized in that: In the gradient heating vacuum degassing process of step 3, the ultrasonic auxiliary device is activated during the heat preservation stage of 180-190℃. The ultrasonic frequency is set to 20-25kHz and the power density is 0.3-0.5W / cm². Ultrasonic vibration can reduce the viscosity of molten flux and accelerate the rise and escape of bubbles. The ultrasonic action time accounts for 60%-70% of the total heat preservation time to avoid excessive spreading of solder paste due to prolonged ultrasonic treatment.

6. The vacuum reflow method for low-void power packaged electronic soldering materials according to claim 3, characterized in that: In the high vacuum isothermal reflow soldering process in step 4, a high vacuum of 1-5 Pa is maintained for the first 40% of the isothermal time, and the vacuum is reduced to 30-50 Pa for the last 60% of the time. Under the premise of ensuring the degassing effect, the excessive volatilization of the low boiling point active components of the flux is reduced, the active atmosphere required for solder wetting is maintained, and the interface defects of poor wetting are avoided.

7. The vacuum reflow method for low-void power packaged electronic soldering materials according to claim 3, characterized in that: In the segmented vacuum cooling and shaping process of step 5, during the first stage of rapid cooling, cold nitrogen gas at a temperature of -5 to 0℃ is introduced into the cavity to form convective cooling. The flow rate of cold nitrogen gas is set in layers along the height direction of the cavity, with the flow rate of nitrogen gas in the bottom layer being 20%-30% higher than that in the top layer. This offsets the vertical temperature difference caused by the rising hot air and improves the cooling uniformity of the workpiece.